(3aGYdjI HQfGeL bGFe Ydi dYH GdCOhGQ ddMO ef HYV GdSdhcjGJ ZjQ GdebHhdI ELJeGYjG ddCWaGd ef(B( 6-5) (3SfhGJ(B/ s - (3fQejf CMeO GdSjO GdMfGhis; (3EjeGf SYO RfGJj (B: s; (3ceGd GdOjf MSjf (B: s ((3GdbGgQI (B: s (3fQejf CMeO GdSjO GdMfGhi (B: s, 2020)
(3JdYH GdOQGeG OhQkG cHjQkG ai MjGI GdWad ShGA cGf Pdc ef NdGd GdCfTWI GdOQGejI GdJi jbhe HgG GdWad ai UhQI EjgGej Ch ef NdGd Jdc; GdYQhV GdOQGejI GdeNUUI ddCWaGd(B. (3ceG jecJ JhXja GdOQGeG ai GdeDSSGJ GdJYdjejI MjK CfgG JYed Ydi RjGOI KbI GdaQO HfaSg HEecGfjGJg hGdJYHjlQ Yf PGJg HGdcdeI hGdMQcI(B: (3ceG JSGYO Ydi feh YOO ef GdbOQGJ GddZhjI hGdYbdjI hfeh GdNjGd(B: (3EcJSGH YOO ef GdNHQGJ hGdJhMO eY GdeKd GdYdjG GdEjLGHjI ai GdeLJeY JNdb dOi GdWad EMSGSkG COHjoG HGdOQGeG JSGYO ai JYOjd GdSdhc hYdGL HYV GdeTcdGJ GdfaSjI hGdCLJeGYjI ddWad h lYJHQ dYH GdOhQ gh CSGdjH GdJYde GdELJeGYj GdPi jJVef JOQjH GdaQO Ydi COGA LhGfH ef GdSdhc GdELJeGYi(B: (3h jSJNOe cCSdhH ai GdYdGL dEYWGA GdWad aQUI efGSHI deeGQSI GdJYGjT hGNJHGQ GdMdhd GdeJYOOI ddeTcdI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdSjGSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCWaGd ef (B5-6 (3SfhGJ s; (3GdOQGeG GdeJNUUI ddWads; (3GdSdhcjGJ ZjQ GdebHhdI ELJeGYjG s